2001
DOI: 10.1002/1097-010x(20010401/30)289:4<266::aid-jez7>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Acclimation to hypoxia increases survival time of zebrafish,Danio rerio, during lethal hypoxia

Abstract: Survivorship of zebrafish, Danio rerio, was measured during lethal hypoxic stress after pretreatment in water at either ambient oxygen or at a lowered, but nonlethal, level of oxygen. Acclimation to nonlethal hypoxia (pO2 ≅ 15 Torr; ca. 10% air‐saturation) for 48 hr significantly extended survival time during more severe hypoxia (pO2 ≅ 8 Torr; ca. 5% air‐saturation) compared to survival of individuals with no prior hypoxic exposure. The magnitude of the acclimation effect depended upon the sex of the fish: hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 15 publications
3
56
2
Order By: Relevance
“…This interpretation is in agreement with that reported by Dykstra et al (1989) and Bone (1978). Several authors reported the prevalence of anaerobic oxidation in white muscles resulting from the limited number of mitochondria (Virani & Rees 2000, Rees et al 2001. The data of the present study showed that the potential destructive indicator TP gives similar results to that of LPO in both muscle and gill in response to pathogen treatment with various species and routes of administration.…”
Section: Oxidative Stress Biomarkerssupporting
confidence: 73%
“…This interpretation is in agreement with that reported by Dykstra et al (1989) and Bone (1978). Several authors reported the prevalence of anaerobic oxidation in white muscles resulting from the limited number of mitochondria (Virani & Rees 2000, Rees et al 2001. The data of the present study showed that the potential destructive indicator TP gives similar results to that of LPO in both muscle and gill in response to pathogen treatment with various species and routes of administration.…”
Section: Oxidative Stress Biomarkerssupporting
confidence: 73%
“…Differences in survival response to an acute additional stress between fed and starved fish may be related to the energetic expenditure required for the digestion and assimilation of food (Brett and Groves, 1979). In zebra fish, Danio rerio, acclimation to 10% air saturation for 48 h significantly extended survival time during more severe hypoxia (5% air saturation) compared to individuals with no prior hypoxic exposure (Rees et al, 2001). The magnitude of the acclimation effect depended on sex and season, suggesting that hypoxia tolerance in zebra fish (and probably in other fish species) is modulated by genetic and/or environmental factors; as a result, comparisons within and between species are difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Acclimation, a form of reversible phenotypic plasticity, is known to modify the maximum temperature tolerance and hypoxia tolerance of many, but not all, fish species (e.g. Rees et al, 2001;Ford and Beitinger, 2005;Eme and Bennett, 2009;Fu et al, 2011;Petersen and Gamperl, 2011). For example, salmonids appear to have fairly limited capacity for acclimation of these traits as maximum temperature tolerance changes only a few degrees in response to acclimation (Elliott, 1991;Baroudy and Elliott, 1994).…”
Section: Introductionmentioning
confidence: 99%